Representações sociais do medicamento por farmacêuticos - Lima, Rosemary Sousa Cunha (2000)
Public Health Care Service has lacked of an effective action of the medicine specialists, the Pharmacist, for a long time. The industrialization, as a result of natural historical evolution, caused a great change in the Pharmacist's professional life directing his job to its marginal poles, such as the clinical analysis. Aiming at analysing the Social Medicine Representations, it was developed a research with Pharmacists resgistered by Paraíba Pharmacy Council, situated in Campina Grande, who were responsible for pharmacies or drugstores, during the data collecting period (April/00 to August/00). The sample was compose for 60 (sixty) Pharmacists: 56,6% of them had finished graduation for more than 10 years ago; 81,7% were female; 65% were married and 53,4% of the people were above 35 years old. It was used the mixed questionnaire, word association and semi-structured interview to make the methodological triangulation in order to deepen the Social Representation Analysis. The results were analyzed in percentage, frequency and average order of evocation and the interviews were analyzed using thematic content analysis. The words association test evidenced the words health, cure and disease as pertaining to the Central Nucleus and pharmacy, treatment, cares needs, research, relief and social problems as pertaining to the peripheral system of Social Representations. The medicines, the pharmacist actuation, the medicine propaganda and the genericals were been evoked simultaneously in positives and negatives aspects, in the interviews. Beside the categories described above, the Pharmacist's behaviour seemed to be guided by his disappointment of not being able to offer "miraculous" healing formulas anymore. Thus, prevented from doing medicines, these professionals feel far from the real object of their work coming to an existential crisis that conducts their attitudes and results in a deficient actuation.